Socio-Demographic Profile of HIV Patients at Seti Zonal Hospital - Paudel, Bidhan Nidhi; Sharma, S; Singh, G. B.; Dhungana, G. B.; Paudel, P. (Journal of Nepal Health Research Council, 2009)
Background: To tackle with powerful strategies aimed at controlling AIDS epidemic, the virus is finding its new way for devastating human lives through bridge population. At present, migrant laborers are the major carriers of HIV from high risk population to the low risk population. The objective is to study the socio-demographic status of HIV patient visiting Seti Zonal Hospital, Dhangadi.Methods: A descriptive study was carried out from December 2006 to May 2008 in 1099 HIV patients visiting HIV clinic, Seti Zonal Hospital, Dhangadi After taking informed consents, information regarding age, sex, educational status and socio economic status ware recorded in standard register. All the information were entered in to SPSS 11.5 system and analyzed to obtain socio-demographic profiles of the patients.Results: Among 1099 Patients, 54.2% were females. Majority patients were in the age group 31-45 years (54.1%). As high as 86.07% of the patients were from Far Western Region and 14.2% were from Mid Western Region. Regarding occupation, almost 50% of the HIV patients were housewives (42.1%of whom were window) followed by migrant laborers (38.8). As high as 77.0% of the patients were found to be illiterate.Conclusion: It can be concluded that low socio-economic status along with high migration rate of the Far Western Region was found to be the major predisposing factor for increasing vulnerability to HIV infection.  Key words: Dhangadhi;  HIV/AIDS;  Housewives;  Migrants;  Socio-economic status.doi: 10.3126/jnhrc.v6i2.2215Journal of Nepal Health Research Council Vol. 6, No. 2, 2008 Page: 107-110